[Troubled land ; The golden credit card ; Nagalit and bulkan - Lazaro, Cheche (Quezon City Probe Productions, 1991)
Examines and looks at the Land Reform program of the Aquino government; A case of a lost credit card that continues to be used long after it is reported lost; and a stage play about Mt. Pinatubo's wrath.
Troubled land (18 min.) -- The golden credit card 916 min.) -- Nagalit and bulkan (16 min.).
VHS.
Keywords: Land reform -- Philippines -- Cavite; Land use -- Philippines -- Cavite; Credit cards -- Philippines; Industrial accidents -- Philippines